HIV TESTING IN A DISTRICT GENERAL HOSPITAL'S EMERGENCY DEPARTMENT. Issue 12 (23rd November 2015) - Smith, C; Kendall, R
Abstract : Objectives & Background: Princess Royal University Hospital (PRUH) is in Bromley, where local HIV prevalence is 2.5 in 1000. 1 National guidelines recommend considering HIV screening in certain hospital settings, where prevalence is greater than 2 in 1000. 2 It is estimated that 24% of people with HIV remain undiagnosed, 3 with clear benefits of early diagnosis including decreased morbidity, mortality, and healthcare cost. Screening programmes in emergency departments (EDs) may be useful but present challenges, 4 and pilots have run in large EDs 5  but we are unaware of similar schemes in smaller EDs. Methods: For five days in November 2014 between 8 am and 8 pm, we offered an HIV blood test to all patients aged 18–75 attending PRUH ED's walk-in triage. Participants were informed of the result two to three weeks later, and asked for feedback about the study. Any positive results would be followed up by HIV specialist services. Questionnaires regarding perceived acceptability and relevance of testing were distributed to staff working in the department. Results: 112 patients were eligible for the test; of these, 88 (78.6%) accepted and 24 (21.4%) declined. Of the 88 tests performed, we established an accurate result in 76. All 76 (100%) patients tested negative for HIV. We were able to inform 68 patients of their negative result; of the other 8 patients, 2 had died and 6 were not contactable. Results from patient questionnaires showed patients most commonly declined due to recent testing, or perceived low risk status. The majority of staff questionnaire respondents felt routine HIV testing in the ED was beneficial and acceptable. Conclusion: Our results confirm patient acceptability of routine HIV testing in EDs, demonstrated by the high uptake of testing. We did not establish any HIV positive results, which was expected given the sample size and local prevalence. We showed routine HIV testing in EDs is feasible and has a high level of staff acceptability, both of which are promising for continuing routine HIV screening in PRUH. We hope to extend the screening to all medical admissions to the hospital, as recommended by current national guidelines.